2016
DOI: 10.1093/occmed/kqw079
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cancer incidence at a fire training college

Abstract: Dealing with supplied records can be problematic but despite the small numbers, we identified an increased risk of cancer for the high group. The mortality data suggested that there was under-ascertainment for the medium and low groups which underestimated risk and a possible reporting bias for brain cancer. Small cohorts can still provide statistically significant findings when investigating locations for cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The regular and active participation in fire combat has been linked with excess morbidity and mortality among firefighters, being the cardio-respiratory diseases the leading causes of death (Gianniou et al, 2016;Gaughan et al, 2014a, b;Soteriades et al, 2011). Some authors have also associated firefighters' occupational exposure with a possibility of increased risk to develop site-specific cancers, such as leukemia, esophageal, lung, kidney and bladder, skin melanoma, testicular, and urothelial cancer (LeMasters et al, 2006;Daniels et al, 2014;Glass et al, 2016;Golka and Weistenhöfer, 2008;Pukkala et al, 2014;Stec et al, 2018;Youakim, 2006). Furthermore, smoking workers are at a higher risk of suffering from the potential cumulative health risks associated with a regular exposure to fire emissions and tobacco consumption (Fernando et al, 2016;Oliveira et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…The regular and active participation in fire combat has been linked with excess morbidity and mortality among firefighters, being the cardio-respiratory diseases the leading causes of death (Gianniou et al, 2016;Gaughan et al, 2014a, b;Soteriades et al, 2011). Some authors have also associated firefighters' occupational exposure with a possibility of increased risk to develop site-specific cancers, such as leukemia, esophageal, lung, kidney and bladder, skin melanoma, testicular, and urothelial cancer (LeMasters et al, 2006;Daniels et al, 2014;Glass et al, 2016;Golka and Weistenhöfer, 2008;Pukkala et al, 2014;Stec et al, 2018;Youakim, 2006). Furthermore, smoking workers are at a higher risk of suffering from the potential cumulative health risks associated with a regular exposure to fire emissions and tobacco consumption (Fernando et al, 2016;Oliveira et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to recognized or probable carcinogens such as benzene, polycyclic aromatic hydrocarbons (PAHs), and volatile organic compounds (VOCs) are common on the fire ground and during fire combustion [ [6] , [7] , [8] ]. Because of these factors, firefighters experience a greater risk and high proportionate mortality ratio of several forms of cancer such as malignant melanoma and multiple myeloma [ 5 , [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…Firefighters could also be exposed to chemical carcinogens during training fires. A recent study found a dose-response relationship between estimated exposures from training fires and cancer incidence at a fire training college in Australia ( Glass et al, 2016 ). The high exposure group at the fire training college had increased risk of all cancers, testicular cancer, and melanoma compared to the general population.…”
Section: Introductionmentioning
confidence: 99%